Current review towards the new best practices of Corporate Real Estate Management (CREM) in Malaysia - Sulaiman, M. A; Mohd Razali, I. N; Zainol, N. N.; Alias, M. N.; Wan Yusoff, W. Z. (UiTM, 2021)
Corporate Real Estate (CRE) is referring to land and buildings owned by companies which are not primarily in the real estate business used for operational purpose. CRE covers the entire range of activities. Awareness of knowledge of CRE in Malaysia lacks because the researcher found that the operation of properties owned by a few large companies is undermanaged and underused. This review paper focuses on the definition of corporate real estate (CRE), components of CRE, and the current practice in the industry. This paper a desk analysis reviewing the literature on general management of the corporate real estate. By using the secondary data such as Company Annual Report, Previous studies and other relevant sources. There are several different issues to examine along the way, from the business strategies, Constituent and tools to help make the right decisions. It draws a framework for CRE analysis. From this paper, we can find the issue to improve the current practice on the CRE in Malaysia.